Islamic Financial Trust as a Moderating Force Between Development Pressures and Environmental Harm in the Age of Social Value Exchange - Aini, Rija; Yafiz, Muhammad; Kamilah, Kamilah (Celebes Scholar pg, 2025)
This study investigates how the environmental consequences of economic growth and urbanization are shaped by the ethical configuration of financial systems rather than by growth patterns alone. Using data from Indonesia between 2018 and 2023, the research employs moderated regression analysis to examine the role of Islamic finance as a relational mechanism that influences how developmental pressures are absorbed or amplified within ecological systems. The findings indicate that both economic growth and urbanization contribute significantly to environmental degradation. However, when Islamic financial principles are present, the nature of these contributions shifts in important ways. Rather than functioning solely as a funding mechanism, Islamic finance appears to guide behavioral choices by embedding capital within a value system that prioritizes long-term responsibility, fairness in allocation, and sensitivity to collective outcomes. This moderating role reflects not only statistical interaction but a broader shift in how economic and spatial expansion are governed. Sustainability, in this framework, is not treated as an external target but as an internal property of how trust, legitimacy, and environmental ethics are encoded into financial decisions. The study offers a new lens through which the link between development and environmental harm can be understood as contingent upon the normative frameworks that regulate how value is created, exchanged, and sustained.